2006
DOI: 10.1373/clinchem.2005.064386
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Brain Natriuretic Peptide Test and Doppler Echocardiography for Early Diagnosis of Mild Heart Failure

Abstract: Background:The early identification of patients at risk for the development of clinical heart failure (HF) is a new challenge in an effort to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…It should be emphasized, however, that this is based on our subjective judgment and is not the result of a systematic review or a meta-analysis. An overview of typical BNP and NT-proBNP values in different cardiovascular disease states is given in Table 2, and a summary of test characteristics and cut-off levels for BNP and NT-proBNP in different settings is given in Tables 3 and 4 [9,10,23,24,32,36,44,45,54,55,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. It is important to recognize that there is a wide overlap of BNP/NT-proBNP levels in different disease states, and that optimal cut-off levels may depend on settings, clinical questions, and other factors.…”
Section: Applications Of Bnp Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be emphasized, however, that this is based on our subjective judgment and is not the result of a systematic review or a meta-analysis. An overview of typical BNP and NT-proBNP values in different cardiovascular disease states is given in Table 2, and a summary of test characteristics and cut-off levels for BNP and NT-proBNP in different settings is given in Tables 3 and 4 [9,10,23,24,32,36,44,45,54,55,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. It is important to recognize that there is a wide overlap of BNP/NT-proBNP levels in different disease states, and that optimal cut-off levels may depend on settings, clinical questions, and other factors.…”
Section: Applications Of Bnp Testingmentioning
confidence: 99%
“…There are only few studies explicitly addressing the question whether BNP can assist in ruling-in or ruling-out the diagnosis of HF also in primary care or in outpatient clinics [9,[22][23][24]55]. It should be noted that in these studies, the majority of patients can be assumed to have had LV systolic dysfunction, which is more easily to assess than LV diastolic dysfunction, and thus data apply mainly for the evaluation of systolic HF [24].…”
Section: Systolic Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Moreover, the onset of heart failure symptoms is often gradual and may not be appreciated or acknowledged by patients with mild heart failure. Aspromonte and colleagues 17 demonstrated that BNP measurement can effectively rule out heart failure in minimally symptomatic patients referred in a structured manner by general practitioners. By receiver operating characteristic analysis, BNP level showed good diagnostic power to detect heart failure (area under the curve, 0.94-0.98).…”
Section: Established Use Of Bnp Assessment In Outpatient Carementioning
confidence: 99%
“…In this setting, a BNP cutoff of 50 pg/mL increases diagnostic accuracy, with high discriminating power to detect a true decompensated state, even in the presence of other high-risk heart disorders and multidrug treatment. 17 Therefore, if applied correctly in this setting, possible diagnoses of heart failure can be excluded and further investigation can be started in individuals with an elevated BNP value. Not only would this approach result in more accurate diagnoses of new-onset heart failure but it is likely that it would also prove cost-effective, potentially reducing referral for more costly echocardiography (Figure 1).…”
Section: Established Use Of Bnp Assessment In Outpatient Carementioning
confidence: 99%